Reversal interest rate and macroprudential policy - Matthieu Darracq Pariès; Christoffer Kok Sørensen; Matthias Rottner (European Central Bank (ECB), 2020)
Could a monetary policy loosening entail the opposite effect than the intended expansionary impact in a low interest rate environment? We demonstrate that the risk of hitting the rate at which the effect reverses depends on the capitalization of the banking sector by using a non-linear macroeconomic model calibrated to the euro area economy. The framework suggests that the reversal interest rate is located in negative territory of around −1% per annum. The possibility of the reversal interest rate creates a novel motive for macroprudential policy. We show that macroprudential policy in the form of a countercyclical capital buffer, which prescribes the build-up of buffers in good times, can mitigate substantially the probability of encountering the reversal rate, improves welfare and reduces economic fluctuations. This new motive emphasizes also the strategic complementarities between monetary policy and macroprudential policy.
Keywords: E32; E44; E52; E58; G21; 330; Reversal Interest Rate; Negative Interest Rates; MacroprudentialPolicy; Monetary Policy; ZLB